Validation of the Rage Attack Questionnaire-Revised (RAQ-R) in a Mixed Psychiatric Population - Palm, Lisa; Haas, Martina; Pisarenko, Anna; Jakubovski, Ewgeni; Müller-Vahl, Kirsten R. (Frontiers in Psychiatry, 2021)
Rage Attacks (RA) represent a clinically relevant symptom in patients with different psychiatric disorders. However, only recently the Rage Attack Questionnaire Revised (RAQ-R, 22 items, range, 0-66) has been developed as a new instrument for the assessment of RA. This study aimed to validate the RAQ-R in a large mixed psychiatric and psychosomatic sample. We tested internal consistency, convergent and discriminant validity as well as factor structure. In order to further explore the relationship of RA to other psychiatric symptoms, we calculated Pearson correlations between the RAQ-R and several other self-assessments including measurements for general psychological distress, quality of life, depression, anxiety, attention deficit/hyperactivity disorder (ADHD), impulsivity, and self-regulation abilities. Most relevant predictors of RA were examined in a multiple regression with stepwise elimination. In order to assess the manifestation of RA in different psychiatric disorders, group differences between diagnostic categories and healthy controls were calculated. We included 156 patients with a wide and typical spectrum of psychiatric diseases. In this sample, the RAQ-R was found to have excellent internal consistency and strong construct validity (Cronbach’s α=0.97, Average Variance Extracted=0.58). Thus, the RAQ-R was shown to be a psychometrically sound assessment of RA in patients with different psychiatric disorders. Close constructs to RA were found to be aggression and hostility (r=0.68) as well as low frustration tolerance and impulse control (r=0.69). Compared to healthy controls, RA were significantly more common in the psychiatric sample (p<0.001). More specifically, RAQ-R scores in all diagnostic categories assessed were higher compared to controls. Highest scores and effect sizes were found in patients with ADHD and borderline personality disorder (p<0.001). Our results suggest that RA are a common and relevant symptom in many psychiatric disorders. As depression and RA showed only a moderate relation, RA should be distinguished from the concept of anger attacks, which are described as a core symptom of depression.